THE ILLUSION OF DIGITAL IMPUNITY: WHY THE INTERNET IS NOT A LAWLESS LAND - Melo, Andre de Oliveira; de Araújo, Alessandra Gusmão Trajano; de Araújo, Adriana Gusmão Trajano; Nardi, Gustavo Davanco; do Nascimento, Carlos Eduardo (Seven Editora, 2026)
The accelerated expansion of the digital environment has produced a mistaken perception that cyberspace operates beyond the reach of legal systems. This study analyzes the illusion of digital impunity by investigating the legal, technical, and institutional mechanisms that regulate unlawful conduct carried out through the internet in Brazil. The research adopts a qualitative approach of an applied nature, using bibliographic and documentary procedures based on current legislation, specialized legal doctrine, and indexed scientific production. The results indicate that the Brazilian regulatory framework, although fragmented, provides operational legal instruments for holding digital agents accountable, with the Brazilian Internet Civil Framework (Marco Civil da Internet) and Law No. 12,737/2012 serving as the central pillars of this system. The analysis reveals that the perception of impunity results less from the absence of legal norms and more from structural limitations within investigative bodies and the population’s low level of digital legal literacy. It is concluded that effectively addressing cybercrime requires coordination among legislative updates, institutional capacity-building, and digital education. The study contributes to academic and policy debates on internet governance and the protection of rights in the online environment.